Letter to the Editor: First complementary observations by ionospheric tomography, the EISCAT Svalbard radar and the CUTLASS HF radar - Mitchell, C. N.; Walker, I. K.; Pryse, S. E.; Kersley, I.; Mccrea, I. W.; Jones, T. B. (CCSD, 1998)
International audience Experimental results are presented from ionospheric tomography, the EISCAT Svalbard radar and the CUTLASS HF radar. Tomographic measurements on 10 October 1996, showing a narrow, field-aligned enhancement in electron density in the post-noon sector of the dayside auroral zone, are related to a temporal increase in the plasma concentration observed by the incoherent scatter radar in the region where the HF radar indicated a low velocity sunwards convection. The results demonstrate the complementary nature of these three instruments for polar-cap ionospheric studies.